A porphyrin fused to four anthracenes. - Davis, N; Thompson, A; Anderson, H (2011)
We have synthesized a fused tetraanthracenylporphyrin by oxidation of a meso-anthracenyl nickel(II) porphyrin with FeCl(3). This compound exhibits an intense red-shifted absorption spectrum (λ(max) = 1417 nm; ε = 1.2 × 10(5) M(-1) cm(-1)) and a small electrochemical HOMO-LUMO gap (0.61 eV). The crystal structure shows that it forms π-stacked dimers with a short Ni···Ni distance (3.32 Å).